Deorphanization of an odorant receptor revealed new bioactive components for green mirid bug Apolygus lucorum (Hemiptera: Miridae). Issue 5 (4th December 2019) - Khashaveh, Adel; An, Xingkui; Shan, Shuang; Xiao, Yong; Wang, Qi; Wang, Shanning; Li, Zibo; Geng, Ting; Gu, Shaohua; Zhang, Yongjun
Abstract: BACKGROUND: The Apolygus lucorum is one of the most destructive insect pests in China with a wide range of host plants. Interaction of A. lucorum with surrounding environment heavily relies on chemical communication. Deorphanization of receptors involved in odors detection elevates our understanding of the olfactory system of this pest and may help to develop a chemical ecology‐based control strategy. RESULTS: AlucOR80, an odorant receptor (OR) in A. lucorum was newly cloned. Gene expression analysis showed that this receptor was mainly expressed in the antennae and head of both sexes but with a male bias. The Xenopus oocytes heterologous expression system coupled with the two‐electrode voltage‐clamp (TEVC) recording revealed that AlucOR80 was tuned to 21 selected compounds. Furthermore, electroantennogram (EAG) tests confirmed that all 21 ligands of AlucOR80 were electrophysiologically active in antennae of both sexes. Behavioral trials in a three‐cage olfactometer indicated that 16 compounds were behaviorally active, amongst which, 12 components were attractants and four components were repellents for adults of both sexes. Butyl butyrate and Dimethyl disulfide (DMDS) were the strongest attractive and repellant compounds, respectively. Importantly, we found the repellency of 1, 8‐Cineole, S ‐(−)‐ cis ‐Verbenol and (1 S )–(1)‐beta‐Pinene against adults of A. lucorum . CONCLUSION: Although AlucOR80 is a general OR, may play important role in the olfactory perception of A. lucorum . Screening of AlucOR80 ligands by behavioral assay provided valuable insights by which olfactory‐based management approaches could be developed by utilizing the behaviorally active components as attractants or repellents. © 2019 Society of Chemical Industry Abstract : Aluc OR80 was mainly expressed in antennae. Functional study via Xenopus oocyte and TEVC revealed 21 ligands for Aluc OR80. Sixteen chemicals were behaviorally active. Three new repellent were recorded for Apolygus lucorum .